Edukasi dan Pelatihan tentang Pengelolaan Mesin Pengolah Sampah guna Meningkatkan Pemahaman Bagi Kelompok Bank Sampah di Desa Pandes - Angger Bagus Prasetiyo; Kartinasari Ayuhikmatin Sekarjati; Eka Yawara; Wartono; Iman Pradana A. Assagaf; Ikbal Rizki Putra (JNANADHARMA, 2023)
Garbage is a problem that is still ongoing today. Based on data from the Ministry of Environment of the Republic of Indonesia, there is the province of Central Java as the highest waste generation in 2022. Therefore, it is necessary to have waste management activities so that they do not have an impact on the environment. One of the community groups that has carried out this activity is the Real Berkah Garbage Bank group located in Pandes Village, Wedi District, Klaten Regency, Central Java Province. The group has been processing organic waste and inorganic waste. However, the management stopped, because one part of the waste processing machine was permanently damaged. So there is a need for a new engine replacement. To prevent this from happening again, community service activities are also needed to increase the level of public understanding in theory and practice. The method used in this community service activity is the lecture method and the practical method. Through this community service activity, there was an increase in the level of understanding of the lecture method by 80% and an increase in the level of understanding of the practical method by 55%.